Zirconia-Based Biomaterials for Hard Tissue Reconstruction. (28th March 2018) - Tosiriwatanapong, Terawat; Singhatanadgit, Weerachai
Implantable biomaterials are increasingly important in the practice of modern medicine, including fixative, replacement, and regeneration therapies, for reconstruction of hard tissues in patients with pathologic osseous and dental conditions. A number of newly developed advanced biomaterials have been introduced as promising candidates for tissue reconstruction. Among these, zirconia-based biomaterials have gained attention as a biomaterial for hard tissue reconstruction due to superior mechanical properties and good chemical and biological compatibilities. This review summarizes the types of zirconia, advantages of zirconia-based biomaterials for hard tissue reconstruction including bone and dental tissues, responses of tissue and cells to zirconia, and surface modifications for enhanced bioactivity of zirconia. Current and future applications of zirconia-based biomaterials for bone and dental reconstruction, ie, medical implanted devices, dental prostheses, and biocompatible osteogenic scaffolds, are also discussed.